Cumulative Damage Mechanism of Short Fiber type C/SiC under Compression. Issue 1 (January 2021) - Tobata, Yuta; Takeuchi, Shinsuke; Goto, Ken
Abstract: This study investigated cumulative damage mechanisms of short fiber type C/SiC under compression. To measure mechanical properties (unloading modulus and permanent strain) before fracture, repeated loading–unloading tests were conducted using a strain gage. Damage was observed to assess characteristics of crack density, length, number, and propagation angle. Furthermore, relations between mechanical properties and damage characteristics were elucidated by application of Basista's equations and by substituting crack densities inferred from damage observations. Stress–strain relations revealed nonlinear behavior. The unloading modulus did not change, but the permanent strain increased. Cracks propagated mainly between fibers, without fiber fracture, connecting other cracks in the direction of orientation 0 deg to 30 deg to the compressive axis. We estimated permanent strain using Basista's equations and damage characteristics. Estimates roughly agreed with experiment results, suggesting that the permanent strain increase is attributable to closed crack sliding and friction caused by increased crack density.